MOTIVACIÓN LABORAL Y GESTIÓN DE RECURSOS HUMANOS EN LA TEORÍA DE FREDERICK HERZBERG - López Más, Julio (2005)
In the search for the industry competitivity in the New Economy and Management the administrators must design leadership styles and administartive practices of high eficiency and perfomance of human resources. The complexity of the laboral motivation requires approaches that consider personal and enviromental factors. The argumentation on the contributions of a pioneer thinker on this subject like Frederick Herzberg and the interpretation of a tesis work for Magister Degree on our «Facultad de Ciencias Administrativas» intitled : «Diseño y validación de un modelo para la identificación y medición de los factores motivacionales de los trabajadores según la teoría de F. Herzberg», are the motivations on this reflexive article. The practice and modern investigations on management show the motivation as a decisive factor that modern managers include in work relationships that they create and monitorize. The administrative function of the Management is understood as the procedure that influences on people, in order to contribute to achieve the objetives of the individuals and the organization jointly; for this is required to create and the sustenance of a context in which the individuals work together in groups to achieve common objetives.